Metal nanoparticles restrict the growth of protozoan parasites. (12th November 2018) - Adeyemi, Oluyomi Stephen; Molefe, Nthatisi Innocentia; Awakan, Oluwakemi Josephine; Nwonuma, Charles Obiora; Alejolowo, Omokolade Oluwaseyi; Olaolu, Tomilola; Maimako, Rotdelmwa Filibus; Suganuma, Keisuke; Han, Yongmei; Kato, Kentaro
Abstract: The Trypanosoma and Toxoplasma spp, are etiological agents of diseases capable of causing significant morbidity, mortality and economic burden, predominantly in developing countries. Currently, there are no effective vaccines for the diseases caused by these parasites; therefore, therapy relies heavily on antiprotozoal drugs. However, the treatment options for these parasitic diseases are limited, thus underscoring the need for new anti-protozoal agents. Here, we investigated the anti-parasite action of nanoparticles. We found that the nanoparticles have strong and selective in vitro activity against T. b. brucei but moderate in vitro activity against T. congolense and T. evansi . An estimation of the in vitro anti- Trypanosoma efficacy showed that the nanoparticles had ≥200-fold selective activity against the parasite versus mammalian cells. Moreover, the nanoparticle alloys moderately suppressed the in vitro growth of T. gondii by ≥60%. In our in vivo study, the nanoparticles appeared to exhibit a trypanostatic effect, but did not totally suppress the rat parasite burden, thereby failing to appreciably extend the survival time of infected animals compared with the untreated control. In conclusion, this is the first study to demonstrate the selective in vitro anti- Trypanosoma action of nanoparticles and thus supports the potential of nanoparticles as alternative anti-parasitic agents.